Leukaemic infiltration of the mandible in a young girl - RACHAEL E. BENSON, HELEN D. RODD, SARAH NORTH, ALISON R. LOESCHER, PAULA M. FARTHING & MARTIN PAYNE (IAPD and Blackwell, 2007)
This report presents a case of leukaemic infiltration of the mandible in a 10-year-old female of Sudanese extraction.